Almost in Europe? How Finland's Embarrassing Entry into Eureka Captured Policy Change. (9th June 2016) - MITZNER, VEERA
Abstract: Common historical narratives of Finnish European policy emphasise the sudden and dramatic change of 1991–1995, when Finland, as a reaction to the collapse of the Soviet Union, rejected its previously cautious approach and wholeheartedly embraced the goal of joining a unified Europe. This article, however, shows that, already in the mid-1980s, the Finnish political and economic elites questioned the country's position in the Cold War order and took bold steps in order to forge closer relations with Western Europe. A key event was the struggle for membership in Eureka, a novel European project designed to enhance cooperation in high technology.